2019
DOI: 10.1016/j.ijmecsci.2018.10.026
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the cyclic plasticity and fatigue failure behavior of different subzones in CrNiMoV steel welded joint

Abstract: The cyclic plasticity and the low cycle fatigue failure behavior of the weld metal (WM) and base metal (BM) of the CrNiMoV steel welded joint under the strain and stress-control modes were investigated respectively. Significant cyclic softening was observed for both the WM and BM under the low cycle fatigue tests with the two control modes. Besides, obvious ratcheting happened in the WM and BM under the stress-controlled cyclic loading conditions. It is shown that both the WM and BM exhibited lower fatigue str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 48 publications
0
4
0
3
Order By: Relevance
“…Tidak hanya itu saja Sebagian besar piston dari kapal juga terbuat dari baja paduan [10]. Selain dijadikan sebagai material penyusun piston pada kapal, baja paduan juga sering dijadikan sebagai material penyusun rocker arm dan connecting rod [11].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Tidak hanya itu saja Sebagian besar piston dari kapal juga terbuat dari baja paduan [10]. Selain dijadikan sebagai material penyusun piston pada kapal, baja paduan juga sering dijadikan sebagai material penyusun rocker arm dan connecting rod [11].…”
Section: Pendahuluanunclassified
“…KESIMPULAN DAN SARAN Simulasi desain piston dengan material baja paduan menghasilkan deformasi maksimum sebesar 0,000407 mm dan deformasi minimum sebesar 0 mm. Selanjutnya simulasi tegangan normal pada desain piston menghasilkan tegangan normal maksimum sebesar 1,043x10 11 Pa dan tegangan normal minimum sebesar -1,054x10 11 Pa. Serta pada pengujian tegangan geser didapati hasil bahwa tegangan geser maksimum mencapai 1,392x10 10 Pa dan tegangan geser minimum mencapai -1,496x10 10 Pa.…”
Section: Gambar 5 Hasil Simulasi Tegangan Normal Pistonunclassified
See 1 more Smart Citation
“…No additional hardening was observed for Ti‐6Al‐4 V. The current research on non‐proportional hardening mainly adopts strain‐controlled mode. Guo et al 18 looked into the low cycle fatigue failure behavior of the CrNiMoV steel under strain and stress‐control modes. Obvious ratcheting phenomena happened under the stress‐controlled loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 44 conducted an experimental observation to the ratchetting of base material and weld metal in the welded joint made from 304L stainless steel and addressed their fatigue lives by considering various stress levels; the experimental observations 44 showed that not only the ratchetting but also the fatigue life of base material and their dependence on the applied stress level were different from that of the weld metal. Guo et al 45 studied the cyclic plasticity of base material and weld metal in the CrNiMoV steel-welded joint and compared their fatigue lives; the results showed that the ratchetting and fatigue life of weld metal were also different from that of the base material. In Wang et al 44 and Guo et al, 45 the base material and weld metal were treated as a homogeneous material separately, rather than a whole welded joint with heterogeneity, and the ratchetting-fatigue interaction of welded joint had not been discussed, either.…”
Section: Introductionmentioning
confidence: 99%